Improving community welfare through Non-Cash Food Support Programs in Jeneponto Regency, South Sulawesi, Indonesia - Amiruddin Amiruddin; Djamil Hasim (Faculty of Social and Political Science, Universitas Airlangga, 2023)
To improve people’s welfare, policies are needed that can help people get above the poverty line. This study aims to describe how the implementation of the Non-Cash Food Assistance Program can improve the welfare of the people in Jeneponto Regency. This study uses a qualitative research design. Data collection techniques are through observation, in-depth interviews, and documentation. The results of the study show that the Non-Cash Assistance Program in Jeneponto Regency can improve people’s welfare which is marked by a decrease in the percentage of the poverty rate from 14.28 percent in 2021, down in 2022 to 13.73 percent. This decrease in the percentage of the poverty rate has made Jeneponto Regency no longer the Regency with the highest poverty rate in South Sulawesi Province. For services, it was found that e-warongs serving the community had low competence, which affected the quality of food sold by e-warongs to beneficiary families. This study concludes, improvement is needed in determining the target group by setting strict criteria for prospective program recipients, and it is necessary to have a cluster for each category, so that the formulation is also adjusted based on needs. Determination of providers must apply a competition system, so that the quality of basic ingredients is maintained at affordable prices.